University and Business: Disruptive training methodology for Wikiproducers - Arce Ballesteros, Guillermo; Matarín Rodríguez-Peral, Eva; Claudio-Quiroga, Gloria (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This study shows how disruptive training methods (DTM) equip students with skills that facilitate intergenerational and intercultural work. Skills and competences of leading international companies and institutions. A review of the literature on disruptive methodology has been carried out. The result shows how traditional education can be adapted to Wikiproducers and Generation Z students, to help them understand and develop some skills that their training is leaving behind, and that can be critical in their early stages of professional and personal life.